Exploratory study for the alkaline activation of basalt powder as a supplementary cementitious matrix - Gheller,Rafael (2022)
resumo: Portland cement remains the main material of choice in construction due to its thermal, mechanical and durability properties. However, there is growing concern about the large amount of energy consumed and the environmental pollution generated during its production. The objective of this study, therefore, was to evaluate the potential of the fine residual material produced by crushing basalt rocks to form a supplementary cementitious matrix through alkaline activation. Basalt powder with a particle size of less than 53µm was prepared and activated with a sodium hydroxide solution, with a sodium silicate solution as an adjuvant. The curing process of the material was also carried out at 5 temperature levels, 75, 85, 100, 115, 125°C, according to the experimental design. The paste was dry curing at a standard digital laboratory oven for 24 hours. After curing, the compressive strength of the material was evaluated, reaching a mean value of 10.21 MPa for the H5S15T125 mixture at 28 days. The microstructure analysis was performed by X-ray microtomography, presenting the reconstruction of the internal pores and cracks, leading to the conclusion that higher curing temperatures formed more porous matrices, although with more strength. Based on the collected data, the statistical analysis of the design was performed showing that sodium hydroxide and temperature have a statistically significant effect on the response variable compressive strength. As such, the alkali-activation of basalt powder can potentially produce a cementitious material of moderate strength, giving purpose to the residue and reducing the emission of harmful particles into the atmosphere.